THE PRESENCE OF LEPIDOBATRACHUS (ANURA, CERATOPHRYIDAE) IN THE NEOGENE OF THE LA PAMPA PROVINCE, ARGENTINA (Ameghiniana, 2017)
Neogene anuran remains from central Argentina were assigned to Lepidobatrachus, in base on its exclusive combination of maxillary characters. Although it would represent one of the oldest Lepidobatrachus, the age of the anuran bearing beds, attributed to the Fm. Cerro Azul, has been traditionally inferred in base on questioned methodology. The presence in these sediments of some mammals also recovered in other sequences whit known age, allows propose a preliminary Late Miocene age for the fossils. This and others Lepidobatrachus remains suggest that the genus would be already distributed and that a seasonal environment would be developed in the central Argentina by the middle Neogene.